Frictional Behaviour, Wear and Comminution of Synthetic Porous Geomaterials - Hughes, Amy; Kendrick, Jackie E.; Lamur, Anthony; Wadsworth, Fabian B.; Wallace, Paul A.; Di Toro, Giulio; Lavallée, Yan (Frontiers in Earth Science, 2020)
During shearing in geological environments, frictional processes, including the wear of sliding rock surfaces, control the nature of the slip events. Multiple studies focusing on natural samples have investigated the frictional behaviour of a large suite of geological materials. However, due to the varied and heterogeneous nature of geomaterials, the individual controls of material properties on friction and wear remain unconstrained. Here, we use variably porous synthetic glass samples (8, 19 and 30% porosity) to explore the frictional behaviour and development of wear in geomaterials at low normal stresses (≤1 MPa). We propose that porosity provides an inherent roughness to material which wear and abrasion cannot smooth, allowing material at the pore margins to interact with the slip surface. This results in an increase in measured friction coefficient from <0.4 for 8% porosity, to <0.55 for 19% porosity and 0.6–0.8 for 30% porosity for the slip rates evaluated. For a given porosity, wear rate reduces with slip rate due to less asperity interaction time. At higher slip rates, samples also exhibit slip weakening behaviour, either due to evolution of the slipping zone or by the activation of temperature-dependent microphysical processes. However, heating rate and peak temperature may be reduced by rapid wear rates as frictional heating and wear compete. The higher wear rates and reduced heating rates of porous rocks during slip may delay the onset of thermally triggered dynamic weakening mechanisms such as flash heating, frictional melting and thermal pressurisation. Hence porosity, and the resultant friction coefficient, work, heating rate and wear rate, of materials can influence the dynamics of slip during such events as shallow crustal faulting or mass movements.